Pyrrolo[2, 3-d]pyrimidines active as Btk inhibitors. (2nd December 2017) - Musumeci, Francesca; Sanna, Monica; Greco, Chiara; Giacchello, Ilaria; Fallacara, Anna Lucia; Amato, Rosario; Schenone, Silvia
ABSTRACT: Introduction : Btk is a tyrosine kinase dysregulated in several B-cell malignancies and autoimmune diseases, and this has given rise to a search for Btk inhibitors. Nevertheless, only one Btk inhibitor, ibrutinib, has been approved to date, although other compounds are currently being evaluated in clinical trials or in preclinal stages. Area covered : This review, after a brief introduction on Btk and its inhibitors already in clinical trials, focusses on pyrrolo[2, 3- d ]pyrimidine derivatives patented in the last five years as Btk inhibitors. Indeed, the pyrrolo[2, 3- d ]pyrimidine scaffold, being a deaza-isostere of adenine, the nitrogenous base of ATP, is an actively pursued target for Btk inhibitors. The patent literature since 2012 have been extensively investigated, pointing out the general features of the patented compounds and, when it is possible, their mechanism of action. Expert opinion : The recently patented pyrrolo[2, 3- d ]pyrimidines, acting as reversible or irreversible inhibitors, showed a very interesting in vitro activity. For this reason, the development of compounds endowed with this scaffold could afford a significant impact in the search for drug candidates for the treatment of immune diseases or B-cell malignancies.